Lagenorhynchus acutus - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Lagenorhynchus acutus (Gray, 1828). Spicil. Zool., 1:2. TYPE LOCALITY: None given, listed as North Sea, Faeroe Isis. (Denmark) (uncertain) by Gray (1846:36). DISTRIBUTION: North Atlantic: cold temperate waters; L. acutus tends to be distributed to the south of L. albirostris. STATUS: CITES - Appendix II. SYNONYMS: gubernator, leucopleurus, perspicillatus. Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 353, DOI: 10.5281/zenodo.7352970